The Effects of a Real-Time Visual Kinetic Feedback Intervention on Shock Attenuation of the Equestrian Rider's Trunk: A Pilot Study - Elmeua González, Marc; Šarabon, Nejc (Frontiers in Sports and Active Living, 2022)
Augmented feedback (provided by an external source) has been commonly used by practitioners who are introducing or re-educating movement patterns as a valuable tool of instruction. This study aimed to evaluate the effects of real-time visual kinetic feedback on a horse-riding coaching session. Sixteen riders volunteered to take part in this study. They performed a pre-intervention trial, a 20-min coaching intervention, and a post-intervention trial. The participants randomly received a coaching + feedback intervention or a coaching-only intervention. Forces at the bit and stirrups were recorded at trot and canter. Thirteen inertial measuring units were fitted to the horse's forelimbs and poll, to the stirrups, cantle of the saddle, distal part of the bridles, 1st sacrum vertebrae of the rider (S1), 7th cervical vertebrae of the rider (C7), wrists of the rider, and helmet. The shock attenuation (SA) between helmet:saddle and between C7:S1 and absolute force output were calculated. Changes in SA and force output were compared between groups by two-way repeated measures ANOVA (group*time) both at trot and canter. Statistical significance was set at p < 0.05. SA was significantly lower in both groups and conditions after the intervention. C7:S1 SA was significantly lower in the feedback + coaching group at canter and trot, and helmet:saddle SA was significantly lower in the feedback + coaching group at trot than in the coaching group. A significant increase in force was observed in all the groups on the stirrups at trot and canter, but no significant changes were observed on rein forces. Implementing sports wearables that provide such type of information might be of remarkable benefit for the rider's development and performance.